HIỆN TRẠNG LƯỠNG CƯ, BÒ SÁT Ở VÙNG ĐÔNG BẮC VIỆT NAM - Ngật, Lê Nguyên (Nhà xuất bản Nông nghiệp, 2016)
Based on the results of surveys on amphibians and reptiles in provinces: Quang Ninh (Tien Yen) 2006, 2008; mountainous areas of Yen Tu, 2004-2008; Ha Giang-Tuyen Quang-Thai Nguyen provinces, 2003-2009 and publications of different authors, we compiled a list of species of amphibians and reptiles in North - East area of Viet Nam. It includes 109 species of amphibians belonging to 36 genera, 10 families, 3 orders and 169 species of reptiles belonging to 86 genera, 22 families, 3 orders (51,01 percent total species number of amphibians and reptiles in Viet Nam). Among them there are 20 spesies only found in Viet Nam with some endemic species: Paramesotriton deloust, Odorrana bacboensis, Rhacophorus hoanglienensis, Theloderma corticale. There are 44 species only ditributed in North - East area, not in other areas of Viet Nam, some of them are specific species: Odorrana yentuensis, Theloderma lateriticum, Tropidophorus boehmei, Shinisaurus crocodilurus, Amphiesmoides ornaticeps and Cyclemys dentata. Of those, there are 38 species are listed in the Red Data Book of Viet Nam 2007, 13 species are listed in Governmental Decree No 32/2006/NĐ-CP.